Design of Afa Hotel 8 Stories with Steel Construction in Surakarta - Prasetyo utomo, Dwi; , Ir. Abdul Rochman, M.T; , Basuki, S.T., M.T (2015)
Surakarta is a town of tourism in Indonesia. The tourists who come to the city of Surakarta, need a place to stay in order to enjoy the beauty of Javanese culture and historic places in Surakarta. The hotel is a building that is used for the residence for tourists. This final project will be to design the hotel AFA 8 stories in Surakarta with steel construction. In the analysis using direct analysis method. This method is a new method in planning of steel structure. Special moment frame (SMF) are system choose, because special moment frame is a common seismic lateral force resisting system use in steel structure. The special moment frame is the best system in building because the beam can develop the seismic force in the plastic hinge. The reduction beam section (RBS) is the best connection in the special moment frame because the plastic hinge occur in the expected point of beam. This final project explains the design special moment frame and details the seismic specification used in design.. The standard code use for design building are American Standard Codes (ASCE, AISC and ACI). Analysis structure in the design calculation use software ETABS 2015. The pile foundation will use in the building to support the load from column and then transfer it to stiffness soil with 11 m in depth. The result in design dimension of SMF column W14x370, SMF beam W21x132, Non-SMF column W14x257, and Non-SMF beam W21x68 are satisfied to use in the building. Dimension base plate 80 cm x 75 cm x 5 cm is satisfied. The pile foundation with 30 cm x 30 cm diameter are satisfied to resist the load. Sloof use dimension 30 cm x 50 cm. Longitudinalreinforcement use 8D16 and shear reinforcement Ф10-200 mm.